BUKU ILUSTRASI SEBAGAI MEDIA MENGENALKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI KOTA PALEMBANG - Yuniarti Wulandari; Yosef Yulius; Husni Mubarat (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract: The Electronic Information and Transaction Law was first passed through Law No.11 of 2008 before finally being revised with Law No.19 of 2016. Based on the results of the questionnaire distributed, it can be concluded that many teenagers in the city of Palembang still do not know about the ITE Law. For this reason, it is necessary to introduce the ITE Law in order to prevent and avoid crime when accessing the internet and social media. In overcoming this problem, the author uses the design thinking method which consists of several stages, namely emphatize, define, ideate, prototype and test. After going through several stages, producing the main media in the form of illustrated books that summarize various information to introduce the ITE Law with attractive illustrations and bright colors adjusting the target target. The supporting media created in the form of digital and print posters, Instagram feeds, X-Banners, catalogs, stickers, tote bags, keychains, note books, standee mascots, and T-shirts. The creation of these media is expected so that the public is aware of the importance of knowing and implementing the ITE Law.